Pregnancy induces retinal microvascular changes indicating cardio-metabolic stress - Dathan-Stumpf, Anne; Stepan, Holger; Valterova, Eva; Jakubicek, Roman; Berbée, Clara; Seidenspinner, Marie-Louise; Kolar, Radim; Rauscher, Franziska G (Pregnancy hypertension, 2024)
We performed longitudinal examinations of the arterial retinal microvasculature using Adaptive Optics Retinal Imaging in a 30-year-old healthy woman with twin pregnancy from the 23rd week of gestation (wog) to three days postpartum. Two blinded graders recorded the average wall-to-lumen ratio (WLR) of the examined retinal artery. There was a significant increase in the mean WLR over the course of pregnancy followed by a decreasing WLR from the 37th wog. The demonstrated changes in WLR may be an expression of vascular remodeling and adaptation to volume load which indicates that pregnancy can be viewed as a cardiovascular stress test.
Keywords: krevní tlak; dospělí; preeklampsie; Heart; srdce; lidé; hypertenze; Female; Hypertension; Pregnancy; Blood Pressure; těhotenství; arteria centralis retinae; Pre-Eclampsia; Adult; ženské pohlaví; Retinal Artery; Humans